The Catholic Church in Taiwan Problems and Prospects (Christianity in Modern China, 2018)
This book provides a key analysis of the development of the Catholic Church in Taiwan, and considers the challenges it faces in contemporary times. It examines how the 1949 revolution in Mainland China brought a great number of Chinese intellectuals to Taiwan and provided the Taiwan Catholic Church with valuable human asset for theological and liturgical indigenization. This volume considers different aspects of the development of the Taiwan Catholic Church in the context of indigenization, and examines how the multi-faceted aspects of Catholicism in the Taiwan Catholic Church are revealed through history, philosophy, social science, linguistics, music and literature. .